Vascular Inflammation Is Associated with Loss of Aquaporin 1 Expression on Endothelial Cells and Increased Fluid Leakage in SARS-CoV-2 Infected Golden Syrian Hamsters - Allnoch, Lisa (Viruses, 2021)
Vascular changes represent a characteristic feature of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection leading to a breakdown of the vascular barrier and subsequent edema formation. The aim of this study was to provide a detailed characterization of the vascular alterations during SARS-CoV-2 infection and to evaluate the impaired vascular integrity. Groups of ten golden Syrian hamsters were infected intranasally with SARS-CoV-2 or phosphate-buffered saline (mock infection). Necropsies were performed at 1, 3, 6, and 14 days post-infection (dpi). Lung samples were investigated using hematoxylin and eosin, alcian blue, immunohistochemistry targeting aquaporin 1, CD3, CD204, CD31, laminin, myeloperoxidase, SARS-CoV-2 nucleoprotein, and transmission electron microscopy. SARS-CoV-2 infected animals showed endothelial hypertrophy, endothelialitis, and vasculitis. Inflammation mainly consisted of macrophages and lower numbers of T-lymphocytes and neutrophils/heterophils infiltrating the vascular walls as well as the perivascular region at 3 and 6 dpi. Affected vessels showed edema formation in association with loss of aquaporin 1 on endothelial cells. In addition, an ultrastructural investigation revealed disruption of the endothelium. Summarized, the presented findings indicate that loss of aquaporin 1 entails the loss of intercellular junctions resulting in paracellular leakage of edema as a key pathogenic mechanism in SARS-CoV-2 triggered pulmonary lesions.